INSTITUTIONAL CHANGES IN THE FINANCIAL SECTOR OF UKRAINE AS THE BASIC TERMS OF CURRENT TRENDS DEVELOPMENT OF FINANCIAL MARKETING - Нікіфоров, Петро; Поченчук, Галина; Бабух, Ілона (My University, 2019)
Marketing as a theory and practice of financial business is actively integrated into the system of financial markets management. Institutional changes in the financial sector are a factor that actively influences the possibilities of financial marketing, and therefore the analysis of interdependence, interdependence of institutional transformations of the financial market and new possibilities of financial marketing in all spheres of its penetration is essential for a general economic model that will determine the future of Ukraine. The features of financial marketing are the properties of the product, processes and institutions of the financial market, distinguishing the task, the information base and marketing tools in the financial sector. The financial institutions of Ukraine in the marketing plan provide clients with a rather narrow range of financial services, a significant part of which has an unsatisfactory level of quality, legal rights and interests of consumers of these services are not sufficiently protected. The development of the financial sector is hampered by the low capitalization of financial institutions. The system of regulation and supervision should support the stability of the financial sector, which is an essential condition for financial institutions to realize their marketing benefits in business activities. New financial technologies (FinTech) and regulatory technologies (RegTech) provide new opportunities both for the development of financial intermediation and for regulators. It is necessary to improve the normative and legal framework for the functioning of the financial sector and its development strategy in terms of taking into account the growth trends in the FinTech sector in Ukraine and the rapid increase in the number of FinTech start-ups and the expansion of FinTech to the non-banking sector. It is necessary to form the appropriate institutional support for the creation of a marketing system for financial services based on banking institutions, to identify the features of behavioral stereotypes and consumer preferences of users of financial services in order to reconcile the interests of financial market actors based on a client-centric business model.
ІНСТИТУЦІОНАЛЬНІ ЗМІНИ ФІНАНСОВОГО СЕКТОРУ УКРАЇНИ ЯК БАЗОВІ УМОВИ РОЗВИТКУ СУЧАСНИХ ТЕНДЕНЦІЙ ФІНАНСОВОГО МАРКЕТИНГУ
Keywords: financial markets; financial sector; financial institutions; institutional change; financial technologies (FinTech); regulatory technologies (RegTech); internet platforms; business models; FinTech market